Selected readings on economic analysis of industries and natural resources - Yew, Tai Shzee (Universiti Putra Malaysia Press, 2001)
The articles contain in this volume are based on empirical analysis that address issues on industrial regulations, entry barriers, technological progress, productivity and investment in the manufacturing industries, the productivity of the fisheries resource and the demand for tourism services in Malaysia, as well as the efficiency o the fishery in West Sumatra and agricultural loan repayment in Indonesia. The information and analysis contained in this volume will be useful to students, researchers, academics, practising economists and policy planners interested in industrial economics and natural resources.